UPPER AND LOWER LIMBS DISABILITY AND PERSONALITY TRAITS - Jabeen, Tahira; Kazmi, Syeda Farhana; Rehman, Atiq ur; Ahmed, Sajjad (Journal of Ayub Medical College Abbottabad, 2016)
Background: It is believed that the study of personality has the potentials to enhance our prognostic abilities and can better to expose the etiology of mental illness through the relationship of revealed mechanisms. The focus of this study was to investigate and compare the habitual patterns of behavior, thought and emotions of upper and lower limb physically disabled students in terms of personality traits. Methods: This cross sectional study consisted of 100 upper limbs and lower limbs disabled students taken from Kingston school Inclusive Education System Abottabad, Mashal special education system Haripur, Syed Ahmed Shaheed special education center Abottabad, Al-Munir Foundation Mansehra and Hera Special Education System Haripur and 100 normal students taken from Islamic International School Abottabad, Falcon Public School Haripur, Iqra Academy Mansehra and Alhamd International School Haripur of Hazara Division by purposive sampling technique. This study was conducted during the month of June 2013 to May 2014. Goldberg five big personality scale was used for measuring personality traits of physically disabled and normal students. Results: The significant difference of personality traits scores between physically disabled students (M = 139.2, SD=12.0) and normal students (M=184.5, SD=13.2), t (198) =25.3, p<.05 was observed. Conclusion: Normal students have high scores as compared to physically disabled students on big five traits, i.e., Extraversion, Agreeableness, Conscientiousness, Emotional Stability and Openness to Experience. Keyword: Upper limb disability, Lower limb disability, Personality traits